Acral lentiginous melanoma: a skin cancer with unfavourable prognostic features. A study of the German central malignant melanoma registry (CMMR) in 2050 patients. (1st February 2018) - Teramoto, Y.; Keim, U.; Gesierich, A.; Schuler, G.; Fiedler, E.; Tüting, T.; Ulrich, C.; Wollina, U.; Hassel, J.C.; Gutzmer, R.; Goerdt, S.; Zouboulis, C.; et al.
Summary: Background: Acral lentiginous melanoma (ALM) is one of the four major subtypes in cutaneous melanoma (CM). Although ALM has a poorer prognosis than other CM subtypes, the prognostic factors associated with ALM have only been verified in small‐sized cohorts because of the low incidence of ALM worldwide. Objectives: To investigate the clinical characteristics of ALM and to evaluate their prognostic values based on a large dataset from the Central Malignant Melanoma Registry (CMMR) of the German Dermatologic Society. Methods: The Kaplan–Meier method was used to estimate the potential influence of clinical and histological parameters on ALM disease‐specific survival (DSS) curves, which were compared using the log‐rank test. A Cox proportional hazards model was used to identify independent prognostic factors for DSS. Results: In total, 2050 patients with ALM were identified from 58 949 patients with CM recorded by the CMMR with follow‐up data. In multivariate analyses, age ( P = 0·006), ulceration ( P = 0·013), tumour thickness ( P < 0·001) and tumour spread ( P < 0·001) turned out to be significant prognostic factors for DSS in ALM whereas sex, nevus association and level of invasion were not independent factors. Conclusions: ALM has the same prognostic factors as other subtypes of melanoma. Unfavourable prognosis probably derives from the delay in diagnosis in comparison with other melanoma subtypes.